Physical Modelling of Floating Debris Boom - Ngien, S. K.; J. E., Tan; Akbari, Abolghasem; S. W., Ahmad (2015)

(untitled)
Rivers play a very important role as sources of water for human beings besides hosting and sustaining vital ecosystems. Pollution of rivers by solid waste is a problem faced by countries around the world and requires concerted efforts from research to management in order to address it. The purpose of the work described in this article is to study the effectiveness of an experimental floating debris boom in retaining litter within an open rectangular channel. Two types of boom connections and three different boom materials were tested at five different flowrates under different combinations. The results indicated that hinged connection is stronger than drilled-hole connection in connecting the boom to the piers. Among the boom materials studied, Styrofoam proved to be the most effective in capturing the floating debris. In summary, floating debris booms made of Styrofoam and connected by hinged connection gave the best performance and are the most effective for capturing floating trash among the combinations tested.